Evaluation of Drainage System for Inundation Problems at Subdistricts of Lowokwaru, Malang City - Hermawan, Wirda Pratomo Bagus; Mardyanto, Mas Agus (IPTEK Journal of Proceedings Series, 2019)
Malang is a city in East Java with the level of development of rapid settlement areas, the region has grown in areas of land rainwater. The consequence of this development is the emergence of some new inundation in urban areas, one of them in Subdistrict Lowokwaru. Carrying amount inundation problems that occurred during 2018 in the Subdistrict Lowokwaru 4 times. Largely due to the drainage conditions are not maintained and are filled with trash and sediment. The conditions resulted in reduced sewer capacity and are not able to drain rainwater discharge and wastewater. Evaluation of the drainage system in subdistrict Lowokwaru includes analysis of technical and economic. On the technical aspects, hydrology and hydraulic analysis are carried out and evaluates sewer capacity. Economic aspects discuss the funding costs and maintenance operations of the drainage system management, as well as discuss the analysis of feasibility studies by calculating Benefit Cost Ratio and Net Present Value. The analysis showed that there are 21 sewers in condition without sediment that capacity is insufficient and 23 sewers in conditions with sediment are not met or sewer capacity is not technically eligible. It is necessary for a handling plan as an attempt to deal with the sewer capacity to drain the runoff discharge. The evaluation of economic aspects shows that the activity of handling inundation problems in the drainage system in Subdistrict Lowokwaru is feasible. This can be seen from the value of the B / C ratio is 1.83 (greater than 1) and the NPV value is positive